Cavewomen Don't Get Fat : The Paleo Chic Diet for Rapid Results - Blum, Esther (New York Gallery Books, 2013)
Offers a high-protein, hormone-balancing, and detoxifying program that will help readers lose weight, get healthy, and feel good from the inside out.
Include Index
Keywords: Reducing diets -- Women--Nutrition -- High-protein diet